Bilateral relations between the United Mexican States and the European Union. A case of study of the Erasmus mundus program and its impact on mexican students - Gutiérrez, Isac Cruz (2017)
The aim of this research is to analyze if the implementation of the Erasmus Mundus program has created a positive impact on the bilateral relations between the United Mexican States and the European Union in the time frame that goes from 2009 to 2014. The hypothesis that this research is pursuing is if bilateral relations have created a positive impact by implementing the Erasmus Mundus program. This is a longitudinal quantitative and analytical research. Primary sources such as dictionaries, books and scientific journals and secondary sources such as articles and researches are used in order to obtain all the desired information. The source and data analysis are made by descriptive statistics that allow to create a good description of the particular objects. To represent the results obtained there are presented tables and graphics that shown the quantity of Mexican applications in the period that goes from 2009 to 2014. 11% of Mexican applicants are accepted, this is a considerable percentage but there is still so much more to do in order to improve these programs because without any question academic exchange programs allow the progress of a better quality of life and for those who can expand their horizons it makes a better life, a better present and future.